Magmatic evolution and architecture of an oceanic intraplate volcano: Vesteris Seamount, Atlantic Ocean - Beloša, L.; Murphy, D. T.; Ubide, T.; Callegaro, S.; Meyzen, C. M.; Bizimis, M.; Mazzini, A. (Frontiers in Earth Science, 2024)
Vesteris is a large (33 × 27 km) and young (summit age: 0.65–0.010 Ma) intraplate seamount in the Greenland Sea, formed from ocean island basalt (OIB) magmatism. The volcano is composed of alkali basalt, basanite/tephrite, phonotephrite, mugearite, and benmoreite. Its phenocryst assemblage includes clinopyroxene, plagioclase, olivine, amphibole, rare haüyne, and oxides (Ti–magnetite and Cr–spinel), with phenocrysts hosting inclusions of apatite, sulfides (pyrrhotite), and melt. Despite its geological significance, the processes governing magma storage, ascent, and eruption dynamics remain poorly understood. To address this, we conducted detailed micro–chemical analyses of phenocrysts, groundmass microcrysts, melt inclusions, and groundmass glass. Using mineral–melt thermobarometry, we characterized the pre– to syn–eruptive crystallization conditions and reconstructed the architecture of the volcanic plumbing system. Our findings indicate that basanite liquids were primarily stored in the upper mantle (∼6.4 kbar; ∼22 km depth) with evidence of multi-level storage extending to ∼9 kbar (∼30 km depth). Textural and compositional zoning in clinopyroxenes suggests rapid magma ascent, while mafic recharge emerged as a key mechanism for remobilizing evolved clinopyroxene mush. Mafic recharge magmas also introduced early olivine crystals, which were later overgrown by high-Mg clinopyroxene upon mixing with more evolved melts. These results demonstrate that major crystal fractionation occurs in the upper mantle beneath Vesteris, resembling processes observed in low-flux ocean island basalt volcanoes. The evidence for rapid magma ascent highlights the dynamic nature of magma movement within the plumbing system, driven by mafic recharge and crystal-melt interactions.